2020
DOI: 10.1289/ehp7058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PCB126 on Adipose-to-Muscle Communication in an in Vitro Model

Abstract: BACKGROUND: Exposure to coplanar polychlorinated biphenyls (PCBs) is linked to the development of insulin resistance. Previous studies suggested PCB126 alters muscle mitochondrial function through an indirect mechanism. Given that PCBs are stored in fat, we hypothesized that PCB126 alters adipokine secretion, which in turn affects muscle metabolism. OBJECTIVES: We determined a) the impacts of PCB126 exposure on adipocyte cytokine/adipokine secretion in vitro; b) whether adipocyte-derived factors alter glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In the presence of ROS, XMEs may become impaired and thus contribute to the modification of key enzymes involved in muscle energy metabolism and lead to muscle dysfunction [54] . Besides, our lab has highlighted the induction of Cyp1a1 expression in rat muscles and in mouse C2C12 myotubes following PCB126 exposure [40] , [55] . While the expression of CYPs has not been investigated in L6 myotubes or in the current study, DDT and DDE exposure could induce a similar response in muscle cells, a mechanism we can not ignore.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of ROS, XMEs may become impaired and thus contribute to the modification of key enzymes involved in muscle energy metabolism and lead to muscle dysfunction [54] . Besides, our lab has highlighted the induction of Cyp1a1 expression in rat muscles and in mouse C2C12 myotubes following PCB126 exposure [40] , [55] . While the expression of CYPs has not been investigated in L6 myotubes or in the current study, DDT and DDE exposure could induce a similar response in muscle cells, a mechanism we can not ignore.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, one study reported a correlation between the plasma concentrations of some POPs and leptinemia, especially in women, but this relationship was not observed with any PCB congeners [ 66 ]. In rodents, exposure to PCB126 at doses from 0.1 to 10 μg/kg for 15 d was reported to have no effect on leptinemia [ 67 ] while in vitro, leptin secretion was not altered in 3T3-L1 cells exposed for 24 h to low doses of PCB126 (between 1 and 100 nM) [ 38 ]. Our observations, combined with previous reports, support the notions that acute PCB126 exposure does not seem to impact leptin secretion and that PCB126 does not affect the increase in leptin secretion under hypoxia, at least under the experimental conditions we tested.…”
Section: Discussionmentioning
confidence: 99%
“…Gourronc et al [ 40 ] observed a twofold increase in IL-6 secretion in cultured adipocytes following a 48-h exposure to 10 µM PCB126. On the other hand, Loiola et al [ 67 ] showed that a 15-day exposure to PCB126 up to 10 μg/kg decreased retroperitoneal adipose tissue IL-6 mRNA levels in rats, while Caron et al [ 38 ] showed no effect of a 24-h exposure to low PCB126 doses up to 100 nM on IL-6 secretion in 3T3-L1. Interestingly, TCDD, the most potent dioxin, has been demonstrated to repress LPS-induced IL-6 production in bone marrow stromal cells, suggesting that the alleged binding of activated AhR to the IL-6 XRE may, in some cases, downregulate IL-6 expression [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Diabetes Federation showed that the number of people aged 20-79 years with diabetes mellitus (DM) worldwide was estimated to be 463 million in 2019. Almost 90% of these people will have type 2 diabetes mellitus (T2DM), and this number may increase to 700 million by 2045 (Caron, Ahmed et al 2020). Oral antidiabetic agents include sulfonylureas, biguanides, thiazolidinediones, alpha-glucosidase inhibitors, meglitinides and etc (Wu, Huang et al 2019).…”
Section: Introductionmentioning
confidence: 99%